2023
DOI: 10.3389/fnins.2023.1211044
|View full text |Cite
|
Sign up to set email alerts
|

The effects and mechanisms of acupuncture for post-stroke cognitive impairment: progress and prospects

Abstract: Stroke is one of the important causes of both disability and death worldwide, which is very common in older adults. Post-stroke cognitive impairment (PSCI) is a common secondary damage of stroke, which is the main cause of long-term disability and decreased quality of life in stroke patients, which brings a heavy burden to society and families. Acupuncture, as one of the oldest and widely used worldwide techniques in Chinese medicine, is recommended by the World Health Organization (WHO) as an alternative and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…Further research has revealed that NF-κB activation is a feature of models of PSCI, and that inhibitors of NF-κB can notably enhance cognitive function by moderating cell apoptosis. This modulation of the apoptotic pathway serves to inhibit neuronal apoptosis, thereby ameliorating cognitive deficits post-stroke ( Liu et al, 2021 ; Li et al, 2023 ). Moreover, NF-κB plays a pivotal role in the neuroinflammatory response mediated by microglia.…”
Section: The Mechanism Of Microglia Involvement In Pscimentioning
confidence: 99%
See 1 more Smart Citation
“…Further research has revealed that NF-κB activation is a feature of models of PSCI, and that inhibitors of NF-κB can notably enhance cognitive function by moderating cell apoptosis. This modulation of the apoptotic pathway serves to inhibit neuronal apoptosis, thereby ameliorating cognitive deficits post-stroke ( Liu et al, 2021 ; Li et al, 2023 ). Moreover, NF-κB plays a pivotal role in the neuroinflammatory response mediated by microglia.…”
Section: The Mechanism Of Microglia Involvement In Pscimentioning
confidence: 99%
“…Domestic research in the field of TCM has found that acupuncture therapy between different acupoints can significantly reduce the expression of Bax and Fas, the key downstream target genes of the NF-κB pathway in microglia, and inhibit NF-κB-mediated neuronal cell activation. Apoptosis, thereby regulating the apoptotic pathway, inhibiting neuronal apoptosis, and improving cognitive impairment after stroke ( Liu et al, 2021 ; Li et al, 2023 ). Although various drugs and TCM treatments currently bring new hope to the treatment of clinical patients.…”
Section: Microglia-based Approach To Psci Treatmentmentioning
confidence: 99%